Natural Disaster Management Knowledge and Practices of the Rural Communities in Bangladesh - Koli, Kamrunnahar; Begum, Salma; Hossain, Md Shakhawat; Rahisul Islam, Md (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to assess disaster management knowledge and practices among rural residents  in four communities of Pabna and Sirajganj Districts, Bangladesh. A survey of 180 households  was conducted to collect data. Respondents were randomly selected for interviews without  regard to religion or ethnicity. Multistage sampling identified respondents using a structured  questionnaire for data collection. Six key informant interviews (KII) were conducted to gather  qualitative data. Participants included local social elites, religious leaders, government  agencies, and NGOs. Eight case study methods were employed to gather data on natural  disasters over time. Each FGD session involved eight to twelve attentive respondents with  comparable backgrounds who shared their opinions. The emphasis was on acquiring factual  and valuable information verified against other sources. Facilitators employed a discussion  guide and documented the proceedings. Data entry was conducted using MS Access, while  SPSS-20 was employed for data tabulation. The study indicated notable enhancements in  individuals' knowledge, practices, and awareness regarding disaster preparedness, including  food preservation, financial savings, secure document storage, and awareness of nearby safe  shelters. The study indicated notable enhancements in disaster preparedness, early warning  systems, coping strategies, and health and hygiene practices. 98.3% of respondents received  early warning messages during floods, whereas only 25% did so. Neighbours and family  members were the primary sources of early flood warnings. Research shows that  communication media is essential in managing natural disasters. The government should  implement initiatives to enhance community awareness of natural disasters and offer disaster  preparedness training.
Keywords: Natural disaster; disaster management; disaster preparedness; community awareness